Corporate governance and audit fees: Evidence from companies listed on the Shanghai Stock Exchange - Xingze Wu (China Journal of Accounting Research, 2012)
This study uses data from companies listed on the Shanghai Stock Exchange to investigate the relationship between corporate governance and audit fees. Full sample results reveal a significant negative relationship between corporate governance and audit fees, and subsample results further show that corporate governance's influence on audit fees is affected by corporate growth. The negative relationship between corporate governance and audit fees is economically and statistically significant in sample companies that grew moderately during the sample period, and mixed or insignificant in companies that experienced overly fast or negative growth.
Keywords: G38; M42; 650; Corporate governance; Audit fees; SSE Corporate Governance Sector; Corporate growth